Effect of Salinity Stress on Growth and Yield Component of Different Mustard Varieties in Bangladesh (Journal of Environmental Science and Natural Resources, 2025)
Soil salinity is a major constraint affecting crop yield and quality. Among oilseed crops in Bangladesh, mustard is the most important. A study was conducted during the 2021–2022 rabi season at the net house of the Agricultural Botany Department, Patuakhali Science and Technology University (PSTU), to identify salt-tolerant mustard genotypes based on physiological responses, growth, and yield parameters. Six mustard genotypes (V1 = BARI Sarisha-11, V2 = BARI Sarisha-14, V3 = BARI Sarisha-15, V4 = BARI Sarisha-16, V5 = Binasarisha-4, and V6 = Binasarisha-9) were tested under four salinity levels (S0 = 0, S1 = 4, S2 = 6, and S3 = 8 dS m⁻¹). Salinity stress negatively affected physiological traits and seed yield across all genotypes. Leaf area and total dry matter (TDM) decreased under salinity, ultimately reducing yield. However, V4 (BARI Sarisha-16) and V2 (BARI Sarisha-14) exhibited better tolerance, maintaining higher growth and yield. BARI Sarisha-16 had the highest leaf area (452.8 cm²), TDM (9.58 g plant⁻¹), plant height (120.5 cm), siliqua count (106.3 per plant), seeds per siliqua (15.66), 1000-seed weight (3.78 g), and seed yield (4.19 g per plant) under control conditions, followed by BARI Sarisha-14. In contrast, BARI Sarisha-15 and Binasarisha-4 exhibited the lowest growth and yield at the highest salinity level. Overall, BARI Sarisha-16 and BARI Sarisha-14 demonstrated superior salt tolerance and could be recommended for cultivation in the saline-prone coastal regions of Bangladesh.Environ. Sci. & Natural Resources, 14(1&2): 89-95, 2025